Contextos mitopéicos da prosa de Mia Couto nos romances Varanda do Frangipani, O Último Voo do Flamingo e Terra Sonâmbula - Trocha, Bogdan; Charchalis, Wojciech (Studia Romanica Posnaniensia, 2023)
This paper presents an analysis of mythopoeic elements in three novels by Mia Couto. Starting from Mircea Eliade’s definition of myth, we look for elements of the Living Cosmos with its axis mundi, centre and periphery, chaos and harmony and quest in the novels. Such structure of the analysis allows us to consider the cultural colonization and decolonization of contemporary Mozambique. We conclude that the analysis of the mythopoetic schema in Mia Couto’s novels demonstrates a crisis of cultural harmony in the contemporary Mozambican state and nation. On the other hand, however, the mythopoetic reveals a horizon of cultural and traditional models of persistence that save not only from chaos but above all from the dehumanization of society.